Do dividend taxes affect corporate investment? - Annette Alstadsæter; Martin Jacob (Arbeitskreis Quantitative Steuerlehre (arqus), 2014)
We test whether dividend taxes affect corporate investments. We exploit Sweden's 2006 dividend tax cut of 10 percentage points for closely held corporations and five percentage points for widely held corporations. Using rich administrative panel data and triple-difference estimators, we find that this dividend tax cut affects allocation of corporate investment. Cashconstrained firms increase investment after the dividend tax cut relative to cash-rich firms. Reallocation is stronger among closely held firms that experience a larger tax cut. This result is explained by higher nominal equity in cash-constrained firms and by higher dividends in cash-rich firms after the tax cut. The heterogeneous investment responses imply that the dividend tax cut raises efficiency by improving allocation of investment.
Keywords: G30; G31; H25; 330; Investment; Dividend Taxation; Private Firms